Evaluation of risk-based antigen and antibody surveillance strategies and their association with HPAI outbreaks in South Korean duck farms - Ahmad, Saleem; Yoo, Dae Sung (Frontiers in Veterinary Science, 2025)
IntroductionHighly pathogenic avian influenza (HPAI) continues to threaten the poultry industry, particularly in duck farms, where early detection is critical to preventing widespread outbreaks. In South Korea, risk-based antigen and antibody surveillance strategies have been implemented to enhance early warning capabilities. However, the effectiveness of these strategies—especially in terms of testing frequency, timing, and spatial alignment with outbreak risks—remains under-evaluated.MethodsThis study analyzed antigen and antibody surveillance data from South Korean duck farms between 2019 and 2022. Testing frequencies and intervals were assessed across high-risk (October–May) and low-risk (June–September) periods, as well as during non-epidemic (2019–2020) and epidemic (2020–2021 and 2021–2022) seasons. Spatial hotspot analysis (Getis-Ord Gi*) and negative binomial regression were applied to evaluate associations between test patterns and HPAI outbreak occurrence. Additionally, test-to-outbreak intervals were calculated to assess the timeliness of detection.ResultsAntigen testing frequencies were significantly associated with HPAI outbreaks during high-risk periods (coefficient = 0.56, IRR = 1.75, p < 0.001). Hot-spot analysis revealed that cold spots received disproportionately more antigen testing than outbreak hotspots (p < 0.001), indicating a misalignment in surveillance priorities. Despite intensified testing during epidemic seasons, no significant reductions were observed in the time intervals between the last diagnostic test and outbreak onset (p > 0.05), suggesting limited improvement in early detection.DiscussionThe findings highlight both the strengths and limitations of South Korea’s current HPAI surveillance strategy in duck farms. While antigen testing serves as a useful predictor of outbreak risk, the spatial and temporal mismatch between surveillance intensity and actual outbreak distribution undermines its effectiveness. A more adaptive and geographically targeted testing approach is needed to enhance outbreak preparedness and response. These results provide a foundation for optimizing future surveillance strategies to minimize the economic and public health impacts of HPAI.